Factors Explaining Consumer’s Attitudes Towards Buying Counterfeit Drugs in North Cameroon - Tayou, Clémence Kayou; Mamoudou, Halidou; Feudjo, Jules Roger (EuroEconomica, 2022)
The purpose of this research is to identify the determinants of the attitude towards counterfeit drugs and to analyze the effect of this attitude on the purchasing behavior of Cameroonian consumers. The purchase of illicit drugs requires a better understanding of consumer behavior if the authorities are to effectively combat the development of this scourge. Data were collected by questionnaire from 696 households in the cities of septentrional zone of Cameroun. The use of regression tests on the determinants of attitude towards counterfeit drugs. The results reveal that attitude towards counterfeit drugs depends on certain socio-demographic factors, product-related factors, and psychographic factors. However, product-related factors, such as perceived quality and the price differential between the original and the counterfeit drug, are the most important. These results are similar to those of Le Roux (2015). The counterfeit drug market is resistant to anti-counterfeiting campaigns mainly because patients find relief at a lower cost.